Satisfaction of psychologically impaired patients with health-care services: A Saudi Arabian perspective - Alhomrani, Majid; Alsanie, Walaa F.; Abdulaziz, Osama; Salih, Magdi M.; Alamri, Abdulwahab; Asdaq, Syed Mohammed Basheeruddin; Alamri, Abdulhakeem S. (Frontiers in Public Health, 2022)
Psychological problems affect a sizable portion of the population, and they require special care. In the current study, we aimed to assess patient satisfaction with the healthcare system at one of the multispecialty hospitals in Riyadh, Saudi Arabia, as well as to identify potential factors that can have an impact on patient satisfaction. A validated pre-tested questionnaire including features to evaluate general hospital services (HS-6 items), nursing services (NS-3 items), pharmacy services (PS-7 items), and a standard patient satisfaction questionnaire (PSQ-18 item) was administered to patients who had been receiving therapy for their psychological disease for the past 3 months. Using binary and multiple regression analysis, the strengths of the associations between sociodemographic factors and patient satisfaction measures were evaluated. The results were expressed as adjusted odds ratios (AOR), which were deemed significant when the P value was < 0.05. Sixty-six percent of the 258 study participants were men, and sixty percent of them were between the ages of 18 and 35 years. The bulk of survey respondents (74%) were employed, married, and well–educated. Our research revealed that those who were employed (AOR, HS-2.5; NS-2.65, PS-2.32), have a higher education (AOR, HS-2.23, NS-2.63, PS-2.82), male gender (AOR, HS-1.12, NS-1.08, PS-1.86) and between the ages of 18 and 35 years (AOR, HS-1.48, NS-1.53, PS-1.67) were more likely to be satisfied with general hospital, nursing, and pharmacy services. Further, those who were married had 1.43 and 1.21 times more chance of satisfaction with the pharmacy and nursing services, respectively, compared to singles. Additionally, those with employment had odds of being satisfied that were 2.4 times higher, highly educated individuals had odds that were 2.1 times higher, participants between the ages of 18 and 35 had odds that were 1.51 times higher, and men had odds that were 1.41 times higher on the patient satisfaction questionnaire scale (PSQ-18). Overall, the study participants' satisfaction with general hospital, nursing, and pharmacy services was 70, 76.3, and 83.3%, respectively, compared to only 61.2% on the PSQ-18. Participants in the survey awarded the hospital amenities, pharmacy services, and nursing care high ratings. The medical care, however, fell short of expectations. The study's findings suggest that action needs to be taken to enhance healthcare system services, particularly in the psychological departments of the medical organization.